The impact of hands-on prayer activities on the development of gross motor skills and spiritual intelligence in young children - Lita, Lita; Hidayanti, Maria; Jazariyah, Jazariyah; Erviana , Yurita; Wafiq, Wafiq; Nurlatifah, Ira (Universitas Ahmad Dahlan, 2024)
This study aims to describe the design of prayer practice learning activities in the development of gross motor and spiritual intelligence. This research is a type of qualitative research using field research methods. The data collection techniques used were observation, interview and documentation. The data was analysed by reducing data, displaying data and drawing conclusions. The subjects of this study were children aged 5-6 (N=23) RA Al Wardah Majalengka. The results showed that: 1) Learning design: a) Purpose: to develop the developmental aspects of moral religious values and physical motor skills, b) Material: recognition of the obligatory prayer, time, number of rakaats, intention, movement, prayer recitation. c) Methods of conversation and demonstration. e) Evaluation of the process and children's performance. 2) Gross Motor Development Develops as expected, children are able to perform prayer movements (takbir, standing, bowing, prostration, sitting between two prostrations, qunut, tasyahud, salam). 3) Children's spiritual intelligence develops as expected, children are able to memorise, recall and say prayers / prayer readings, children are able to perform prayer. Its activity positively impacts gross motor development, spiritual intelligence, cooperative attitudes, language skills and moral and religious values of early childhood.